What are the contraindications to the influenza vaccine?. Issue 6 (June 2015) - Misbah, Shaheen; Kirchoff, Elizabeth
Abstract : Evidence‐Based Answer : Low‐albumin, seasonal trivalent influenza vaccine (TIV) appears safe for patients with egg allergies (SOR: B, RCT and case series). It also appears safe for patients with a history of Guillain‐Barré syndrome (GBS) (SOR: C, retrospective cohort trial). Immunocompromised patients also benefit from influenza vaccination and generally the vaccination is well tolerated (SOR: A, systemic review of RCTs).